1992
DOI: 10.1002/hep.1840160627
|View full text |Cite
|
Sign up to set email alerts
|

APF/CBP, an anionic polypeptide in bile and gallstones that may regulate calcium salt and cholesterol precipitation from bile

Abstract: The article in this issue of HE;PATOLOGY by Kestell et al.(1) is a welcome confirmation of the presence in bile and gallstones of a small anionic calcium-binding biliprotein -APFiCBP (anionic polypeptideicalcium binding protein) -origmally discovered by Lafont and her co-workers in Marseille (2, 3 ) as a result of their interest in hepatic lipoprotein transport and, later, in our laboratory in Chicago (4, 5 ) as a result of our hypothesis that gallstones are a biomineralization system (4, 6). This editorial wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Such matrix proteins have been reported in pancreatic and renal calculi []. A low‐molecular‐weight (<12kDa) acidic glycoprotein isolated from hepatic bile, gallbladder bile, cholesterol gallstones, and pigment stones, denoted an anionic polypeptide/calcium‐binding protein (APF/CBP), has been found to display calcium‐binding properties [].…”
Section: Introductionmentioning
confidence: 99%
“…Such matrix proteins have been reported in pancreatic and renal calculi []. A low‐molecular‐weight (<12kDa) acidic glycoprotein isolated from hepatic bile, gallbladder bile, cholesterol gallstones, and pigment stones, denoted an anionic polypeptide/calcium‐binding protein (APF/CBP), has been found to display calcium‐binding properties [].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that APF is involved in the uptake of unesterified cholesterol (15) and stimulates cholesterol and PL transport to the bile (16,17). It was also recently demonstrated that APF plays an important role in controlling the onset and rates of precipitation of calcium salts, bile pigments, and cholesterol in gallstone formation (18,19).…”
mentioning
confidence: 99%
“…As it is found in hepatic bile, this factor is likely to be of hepatic origin. Other non-mucin factors have crystallisation promoting effects in vitro: a pronase resistant low density lipoprotein particle (±90% lipid),42 aminopeptidase N (a 130 kDa biliary canalicular glycoprotein),43 44 phospholipase C,45immunoglobulins of the IgM, IgA and IgG classes,46-48fibronectin,49 a biliary anionic polypeptide fraction (APF),50 acute phase proteins, such as a 42 kDa α 1 -acid glycoprotein,51-54α 1 -antichymotrypsin, 55 and haptoglobin. 56 Although the liver secretes promoting and inhibiting factors simultaneously, the ultimate pathophysiological importance of these proteins in human bile remains controversial 51.…”
Section: Biliary Proteins and Cholesterol Crystallisationmentioning
confidence: 99%